Community Movement Assistance in Achieving Healthy and Clean Lifestyle Behavior to Prevent Stunting in Tabunganen Tengah Village, Tabunganen District, Barito Kuala - Annisa Annisa; Ahmad Zaini; Aulianza Salsabila; Dian Jaya Lelana4; Meliya Cahya; Muhammad Rifqa; Najwa Amelia7; Nurul Janah Istiqamah; Rachil Fadhilah; Rizky Gunawan (Borneo Community Development, 2024)
The level of stunting in Indonesia, especially in South Kalimantan, is still relatively high and needs serious attention from all parties. In this case there are several ways to prevent and deal with stunting in several areas in South Kalimantan, namely changing lifestyles to be health and celan, taking blood supplement tablets, and others. The population in this study were residents of Tabunganen Tengah Village, Tabunganen District, Barito Kuala Regency.